International Context of Configuring Integrated Social Policies: Terminological Clarifications and Measurement Possibilities - Zamfir, Elena (Calitatea Vieții, 2019)
This paper focuses on the multiple influencing of the individual and societal wel-being by both economic and non-economic social factors which stimulated the development of some composite-aggregate indicators centered on the specifics of social justice and the quality of life. Harmonizing the psycho-sociological, economic, and political theories regarding quality of life with a new, wide statistical database (synthetic, global indicators) opens actual opportunities for correlating sectoral social policies at global level, right at the time of their design. So, specific indicators were developed for social justice, equal opportunities, and inclusion, etc. in the framework of some database accessible in real time to all member countries of the EU. In fact, the presence of synthetic/output and aggregated social indicators (social inclusion, social justice, happiness, etc.) measures the impact of the social policies on the individual/societal wel-being, and as regards life satisfaction of the individuals within a community (Precupeţu and Voicu M. 2005, Zamfir E. and Magino 2013). These indicators can measure not only the current state, the simple static presentation of the situation in the living conditions of the population, but also its dynamics over time, as continuous process of changes and improvements brought to the quality of life. Maslow’s pyramid of needs, the general systems’ theory, sociologic and anthropologic functionalist and structuralist theories, as well as the modern life satisfaction theories become explanatory theoretic milestones for supporting interactive and balanced policies. Moreover, only by the mutual determination and inter-conditioning relationship of the sectoral policies supported by multiple social indicators, the general changes over time might be evaluated for the quality of life.